Theory of flight - Von Mises, Richard, 1883-1953 (Dover Publications, 1959)
Perhaps the most balanced, well-written account of fundamental fluid dynamics ever published. Mises' classic avoids the formidable mathematical structure of fluid dynamics, while conveying? by often unorthodox methods? a full understanding of the physical phenomena and mathematical concepts of aeronautical engineering. An outstanding textbook.? Scientific, Medical and Technical Books.
"Unabridged and unaltered republication of the English translation first published ... in 1945."
Keywords: Aerodynamics.; Airplanes.; Flight.; elektronické knihy; electronic books